PERILAKU KONSUMSI SUSU PADA IBU HAMIL - Mustika Nilam Sari; Retnaningsih Retnaningsih (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2008)
Pregnant woman with her physiological state is a potential group as milk consumer. The aimed of this research was to study milk consumption behavior among pregnant women. Sampling technique used accidental sampling and choose 300 pregnant women as samples. All data was collected by interview using questionnaire. Inferential statistics included Chi Square and Rank-Spearman Correlation were used for analyzing. The milk forms which consumed include powder, condensed and fresh milk. Most of milk product consumed by samples had label, except for fresh milk. Supermarket as a place to buy was chosen by most of the samples. Nutrition fact was the main attribute concerned in choosing and buying milk. Most of samples (85.0%) consumed milk for health reason. Milk consumption frequency only had significant positive correlation with knowledge level and household expenditure. Amount of milk consumption had significant positive correlation with education, nutrition knowledge of mother and household expenditure; but had significant negative correlation with family size. Education had correlation with kind, form, main attribute of milk and place to buy milk. Milk expenditure correlated with kind and form, main attribute of, and reason to consume milk. Income correlated with kind, form of and place to buy milk